Toxicological Risks of Agrochemical Spray Adjuvants: Organosilicone Surfactants May Not Be Safe - Mullin, Christopher A.; Fine, Julia D.; Reynolds, Ryan D.; Frazier, Maryann T. (Frontiers in Public Health, 2016)
Agrochemical risk assessment that takes into account only pesticide active ingredients without the spray adjuvants commonly used in their application will miss important toxicity outcomes detrimental to non-target species including humans. Lack of disclosure of adjuvant and formulation ingredients coupled with a lack of adequate analytical methods constrains the assessment of total chemical load on beneficial organisms and the environment. Adjuvants generally enhance the pesticidal efficacy and inadvertently the non-target effects of the active ingredient. Spray adjuvants are largely assumed to be biologically inert and are not registered by the USA EPA, leaving their regulation and monitoring to individual states. Organosilicone surfactants are the most potent adjuvants and super-penetrants available to growers. Based on the California Department of Pesticide Regulation data for agrochemical applications to almonds, there has been increasing use of adjuvants, particularly organosilicone surfactants, during bloom when two-thirds of USA honey bee colonies are present. Increased tank-mixing of these with ergosterol biosynthesis inhibitors and other fungicides, and with insect growth regulator insecticides may be associated with recent USA honey bee declines. This database archives every application of a spray tank adjuvant with detail that is unprecedented globally. Organosilicone surfactants are good stand alone pesticides, toxic to bees, and also present in drug and personal care products, particularly shampoos, and thus represent an important component of the chemical landscape to which pollinators as well as humans are exposed. This mini review is the first to possibly link spray adjuvant use with declining health of honey bee populations.